2012
DOI: 10.1016/j.jep.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antiulcer activity of chromanone fraction from Calophyllum brasiliesnse Camb

Abstract: The results indicate that BI is partly responsible for the HECb antiulcer and anti-Helicobacter pylori effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 35 publications
4
18
0
3
Order By: Relevance
“…In contrast, the GSH levels were significantly decreased in the EtOH group compared with the normal control, whereas the BCT treated group had higher GSH levels than the EtOH group. These differences are compatible with previous studies [21,27,29]. …”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the GSH levels were significantly decreased in the EtOH group compared with the normal control, whereas the BCT treated group had higher GSH levels than the EtOH group. These differences are compatible with previous studies [21,27,29]. …”
Section: Discussionsupporting
confidence: 93%
“…Lemos et al (2012) showed a fraction containing a mixture of chromanone acids from C. brasiliense stem bark prevented the gastric ulceration caused by ethanol and indomethacin treatments due to reduction of malondialdehyde and catalase levels in the gastric tissue. However, partial inhibition of H. pylori growth was observed by a hexane extract and a mixture of chromanone acids, indicating that both fractions possess some anti-H pylori activity (Lemos et al, 2012).…”
Section: Cocculus Hirsutusmentioning
confidence: 98%
“…In order to investigate the effect of solvent polarity upon the photoproduct formation, we have carried out the photolysis of 2-thienyl/furyl-3-butenyl/butynyl-bischromones (Kumar and Yusuf, 2010) 91 (Scheme 22) in dry propan-2-ol:THF…”
Section: Photoisomerizationmentioning
confidence: 99%
“…When the photoreactions were carried out in dry benzene, only cyclized products were isolated and no product similar to vinyl ethers 96 was observed. Similarly, 2-phenyl/tolyl/anisyl-3-butenyl/butynyl-bischromones (Kumar and Yusuf, 2009) 95 also generated four types of new photoproducts 96-98 (Scheme 23). The photochemical transformation of these bischromones was found to be dependent upon the nature of the 2-aryl ring and H-donating capability of the solvent.…”
Section: Photoisomerizationmentioning
confidence: 99%
See 1 more Smart Citation